2018
DOI: 10.3750/aiep/02485
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the striped seabream, Lithognathus mormyrus (Actinopterygii: Perciformes: Sparidae), in the central coast of Algeria, Mediterranean Sea

Abstract: Background. Striped seabream, Lithognathus mormyrus (Linnaeus, 1758), is a bony fish, which has a high economic value on the Algerian coast. Because of the increasing fishing pressure, however, a close monitoring is recommended. The information about the biology of this species, occurring in the southwestern Mediterranean Sea and especially in the north African coast, is very limited. The presently reported study provides new estimated data on age and growth parameters of striped seabream in Algeria. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The relationship between length and weight for this species shows that growth shows negative allometry (b = 2.9475) for combined sexes. Suau (1970) reported positive allometric growth (b = 3.43) in the study conducted from Spanish coasts, Kraljević et al, (1995) in the northern Adriatic isometric growth (b = 3.05) and in the central Adriatic negative allometric growth (b = 2.69), again Kraljević et al, (1996) from northern Adriatic reported isometric growth, Türkmen & Akyurt (2003) reported isometric growth (b=2.979) in their study conducted in Iskenderun Bay, Monteiro et al, (2010) from coasts of Portugal reported isometric growth (3.023), Sümer et al, (2014) reported isometric growth (2.999) from Antalya, Aydın (2017) reported negative allometry from the Black Sea (2.398) and Boufersaoui et al, (2018) reported isometric growth (3.094) from coasts of Algeria (Table 4). Even though isometric growth was reported by almost all the previous studies, there are some differences.…”
Section: Discussionmentioning
confidence: 90%
“…The relationship between length and weight for this species shows that growth shows negative allometry (b = 2.9475) for combined sexes. Suau (1970) reported positive allometric growth (b = 3.43) in the study conducted from Spanish coasts, Kraljević et al, (1995) in the northern Adriatic isometric growth (b = 3.05) and in the central Adriatic negative allometric growth (b = 2.69), again Kraljević et al, (1996) from northern Adriatic reported isometric growth, Türkmen & Akyurt (2003) reported isometric growth (b=2.979) in their study conducted in Iskenderun Bay, Monteiro et al, (2010) from coasts of Portugal reported isometric growth (3.023), Sümer et al, (2014) reported isometric growth (2.999) from Antalya, Aydın (2017) reported negative allometry from the Black Sea (2.398) and Boufersaoui et al, (2018) reported isometric growth (3.094) from coasts of Algeria (Table 4). Even though isometric growth was reported by almost all the previous studies, there are some differences.…”
Section: Discussionmentioning
confidence: 90%
“…• Biomass • Medits, Dufour et al, 1995 • K andL∞ • Erguden et al, 2016;Hussein et al, 2011;Meti̇n et al, 2011;Nash, 1982 • Diet • Bell & Harmelin-Vivien, 1983;Cresson et al, 2014;Gibson & Ezzi, 1979 Akyol, 2001;Boufersaoui et al, 2018;Campillo, 1992;Duman & Basusta, 2013;Félix et al, 2011;Kaya & Başusta, 2016;Kozul et al, 2001;Matić-Skoko et al, 2011;Morales-Nin & Moranta, 1997;S. I. Rizkalla & Bakhoum, 2009;Valeiras, Macías, et al, 2008;Vassilopoulou & Papaconstantinou, 1992• Diet • Abdel-Aziz, 1994Campo et al, 2006;Capapé et al, 2007;Capezzuto et al, 2021;Matallanas et al, 1995;Morales-Nin & Moranta, 1997;Morato et al, 2001;Papaconstantinou & Caragitsou, 1989;S.…”
Section: Table Des Figures Et Tableauxunclassified
“…Weight-length relationships were estimated for the striped seabream from the Mediterranean coast of Spain (Suau, 1970), Gokova Bay (Ceyhan et al, 2008), Adriatic Sea (Maci et al, 2009) and Gulf of Gabes (Ghailen et al, 2010). Reproduction and growth have been investigated in the western Mediterranean (Suau, 1970), northern and central Adriatic Sea (Kraljević et al, 1996), central-eastern Atlantic (Lorenzo et al, 2002;Pajuelo et al, 2002), Iskenderun Bay (Türkmen & Akyurt, 2003), coastal waters of the Thracian Sea (Kallianiotis et al, 2005), Beymelek Lagoon (Emre et al, 2010), south-eastern coast of Tunisia (Ben Abdallah-Ben Hadj Hamida et al, 2016) and in the central coast of Algeria (Boufersaoui et al, 2018).…”
Section: Introductionmentioning
confidence: 99%